Oral/oropharyngeal “selfies” in gay and bisexual men: a pilot study exploring oropharyngeal screening for HPV-related possible malignancies - Ross, Michael W.; Bennis, Sarah L.; Nichols, C. Mark; Zoschke, I. Niles; Wilkerson, J. Michael; Rosser, B. R. Simon; Stull, Cyndee L.; Nyitray, Alan G.; Flash, Charlene; Khariwala, Samir S. (Frontiers in Public Health, 2023)
Objectives This study aims to determine the potential uptake and quality of oropharyngeal “selfies” taken by gay/bisexual men as a screening approach for HPV-associated oropharyngeal cancer. Methods From 1,699 gay/bisexual men in the US, surveyed about knowledge and attitudes to HPV-associated oropharyngeal cancer, a random sample of 320 men were invited to take an oropharyngeal “selfie” by smartphone and send it to the study website: 113 (35.5%) did so. Images were rated for quality by three healthcare professional raters blinded to each other's rating, with an otolaryngologist as the gold standard. In the second wave, those whose images were rated as unacceptable were sent a short instructional video and asked to send another image. Of the 65 invited, 46 did so. An additional 15.2% sent acceptable images, and a total of 28.3% of the sample was acceptable. Results A total of 1,121 men willing to participate in the future study who believed they could take a quality “oral selfie” were potentially eligible for this activity. A random sample of 320 participated: 153 participants started (47.8%) and 113 participants (35.3%) submitted an image. Responders were more likely to be younger, have higher knowledge scores on oropharyngeal HPV-related cancer, and have had HPV vaccination. There was high agreement between the three raters. Images of good/acceptable quality were 22.1%; oropharynx partially occluded images were 29.2%; oropharynx not visible images were 18.6%; images too dark were 21.2%; and images too small were 8.8%. From the second wave of requests with instructional videos, an additional 15.2% sent in quality images, with the remaining issues being partial occlusion of the tonsils by the tongue. Conclusion One-third of the invited gay and bisexual men sent oropharyngeal selfie images to the study website and a total of 28.3% were of clinically acceptable quality. Following an instructional video on poorer-quality images, additional quality images were received. One barrier, i.e., partial occlusion of the oropharynx by the tongue remained. Quality oropharyngeal “selfies” are obtainable online.